First year medical students' perceptions of the impact of wearing scrubs on professional identity: a narrative analysis in the United Arab Emirates. Issue 11 (3rd November 2020) - Sorrell, Sara; Ibrahim, Halah
Abstract : Objectives: Medical school serves as a critical developmental period for future physicians, during which students begin to form a professional identity. Just as personal appearance, particularly clothing, is an important external expression of one's personal identity, 'uniforms' in healthcare, including white coats and scrubs, symbolise status and a group identity. There are, however, limited studies on the impact of physician attire on medical students' formation of professional identity. Accordingly, through qualitative analysis of written narratives, we sought to analyse medical students' experiences of wearing professional physician attire, namely scrubs, and how the uniform impacted their confidence level, performance and behaviours, as well as their identity as future physicians. Design: Qualitative analysis of medical student's written narratives. Setting: Khalifa University College of Medicine and Health Sciences (KU CMHS) is a new medical school in the United Arab Emirates, with an inaugural class of 30 students admitted in August 2019. It is the only medical school in the city of Abu Dhabi, and the only school in the country that follows a postgraduate medical curriculum. Participants: All first year medical students at KU CMHS were purposively sampled. Methods: Students completed a voluntary online anonymous questionnaire. We employed a social identity approach to data analysis. Thematic content analysis was conducted on their narratives to identify themes. Results: We identified three major themes, namely (1) emotions, (2) logistics and (3) interpersonal relationships. Conclusions: Medical students form early perceptions regarding physician attire and its impact on their professional identity. Engaging in conversations regarding professional attire with educators or mentors could provide an important opportunity for students to discuss and explore professional identity early in training.